Profil Penjelasan Ilmiah Siswa SMA pada Materi Sistem Peredaran Darah Manusia - Lilya Vany Wisma Widiana; Baskoro Adi Prayitno; Bowo Sugiharto (Postgraduate, University of Mataram, 2024)
This study aims to determine the profile of scientific explanation ability of high school students, especially on the material of the human circulatory system. The type of research used is quantitative research with survey methods shared through google forms. The subjects of the study were high school students who had received human circulation system material in one of several schools in Central Java, the research sample was selected through random sampling techniques from the population. The research instrument used was adapted from McNeill, Lizotte, Krajcik, and Marx (2016) which consisted of 9 long answer questions to be able to determine the success of aspects of claim, evidence, and reasoning in scientific explanation. The instrument has been declared valid and reliable through Rasch Model testing. The research data is in the form of scores from student answers which are then processed through the Rasch Model to determine the level of difficulty and wright map person (students) to find out the profile of each student's scientific explanation ability. The results showed that 78% of students were still at the lower middle level in compiling the three aspects of scientific explanation, and only 12% of students were able to achieve maximum scores in the preparation of claims, evidence, and reasoning.